1998
DOI: 10.1086/314438
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Human Antibody Responses to Culture Filtrate Antigens ofMycobacterium tuberculosis

Abstract: This study was undertaken to define the antigens in culture filtrates of actively replicating Mycobacterium tuberculosis that are recognized by antibodies from tuberculosis (TB) patients. Two-dimensional Western blots were probed with sera from healthy controls and TB patients that were preabsorbed with Escherichia coli lysates to deplete cross-reactive antibodies. Antibodies from TB patients recognized 26 of the >100 culture filtrate proteins, and the repertoire changed with disease progression. Only 12 of 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 12 publications
7
68
0
Order By: Relevance
“…It has been previously shown that active TB patients display circulating IgG Ab against several Mtb secreted molecules [40,41]. In the present work, we have shown that active TB patients presented high titers of anti-sMTL-13 IgG, a response that decreased following therapy.…”
Section: Discussionsupporting
confidence: 66%
“…It has been previously shown that active TB patients display circulating IgG Ab against several Mtb secreted molecules [40,41]. In the present work, we have shown that active TB patients presented high titers of anti-sMTL-13 IgG, a response that decreased following therapy.…”
Section: Discussionsupporting
confidence: 66%
“…38 kDa, a major protein present in culture filtrates of M. tuberculosis, has been studied extensively (1,17,22). Several studies have shown an association between the presence of anti-38 kDa antibodies and advanced cavitary TB (14,22,75). In smear-positive patients, recombinant 38 kDa yielded a sensitivity of 47% (95% CI, 39 to 55) and a specificity of 94% (95% CI, 86 to 98) (8,27,33,35,37,55,77,81).…”
Section: Resultsmentioning
confidence: 99%
“…These data are in the range of those of other studies that examined humoral immunity to recombinant M. tuberculosis proteins, whereby, depending upon the antigen evaluated and its method of production, the sera of 12 to 58% of TB patients were found to contain specific antibodies (38,41). Overall, the available data indicate that the spectrum of M. tuberculosis antigens recognized humorally varies dramatically between patients (41,58). One contributing factor is the expansion of the repertoire of humoral specificities to M. tuberculosis antigens as TB progresses (2,58).…”
Section: Vol 71 2003mentioning
confidence: 99%